2022
DOI: 10.3390/foods11030408
|View full text |Cite
|
Sign up to set email alerts
|

Eating Habits during the COVID-19 Pandemic and the Level of Antibodies IgG and FRAP—Experiences of Polish School Staff: A Pilot Study

Abstract: The coronavirus 19 (COVID-19) pandemic has brought many changes in terms of lifestyle, education, stress levels, and social contacts. The aim of our research was to evaluate changes in eating habits, physical activity, and selected lifestyle elements in a group of school staff, as well as their immune response to vaccination against COVID-19, and FRAP (ferric reducing antioxidant power) level. In total, 108 primary school teachers and other school staff with integration departments were included in the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Initiatives aimed at reducing lead exposure, such as strengthening hand hygiene, environmental rehabilitation, and conformity testing of industrial materials and waste, may have significant implications for protecting sleep health. As a result, body energy and immunity can be maintained [ 44 ]. We also observed a correlation between hypertension and sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Initiatives aimed at reducing lead exposure, such as strengthening hand hygiene, environmental rehabilitation, and conformity testing of industrial materials and waste, may have significant implications for protecting sleep health. As a result, body energy and immunity can be maintained [ 44 ]. We also observed a correlation between hypertension and sleep disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Contrarily, reduced or unchanged alcohol use was reported in a few studies [89,[94][95][96][97]. Moreover, elevated consumption of water, fruits, vegetables, and nuts was reported in a group of Polish primary school teachers [94] and Serbian students [95]. Notably, the most profound changes in the structure of consumed food were observed in the individuals who feared COVID-19 infection and strictly followed the isolation rules [98].…”
Section: Central and Eastern European Countriesmentioning
confidence: 93%
“…As for dietary composition, most studies revealed that consumption of fast-food products, instant soups, sweet beverages, and energy drinks decreased, while a concomitant increase in sweets, eggs, potatoes, canned meat, and alcohol was noted [87,89,91,93]. Contrarily, reduced or unchanged alcohol use was reported in a few studies [89,[94][95][96][97]. Moreover, elevated consumption of water, fruits, vegetables, and nuts was reported in a group of Polish primary school teachers [94] and Serbian students [95].…”
Section: Central and Eastern European Countriesmentioning
confidence: 99%